The Babis and Baha'is in Iran - المدرس المساعد وئام شاكر غني (College of Education for Women, 2019)
The person who wants to learn. The history of Bab'is will notice a very starnge phenomenon that they (Babis and Baha'is) resort to visions to prove their delusion. The believers usually reach to each other by their visions. This phenomenon are shared among them from Al- Ahsa'ai time till the last phase of their propaganda which is the Baha'is propaganda, and this is due to their ignorance and under development in doctrine of islam which was widespread in Iran and the Islamic world. The whole secrets of Babis and Baha'is movement were restricted among particular group, most of them were Al- Rashti's students and knew the basic principles of their movement which deperding or (the principles) declaration of old internal opinions, leaving the Islamic worhips and distort sharia. Besides the role of the colonial countries, those put the plans to destroy the Islamic religion, they have the wapper and stronger hand in supporting and this movement with money and weapons and establishing it. So the Baha'is movement considered the higher stage in the historical plot stages against Islam, beginning with internal magicians and ending with internal modern which directed by the christianity preachers systems and the global zionism Masony systems.